Bedside Handover as an Effort to Improve Nurses' Communication in Providing - Gurning, Yanty; Siregar, Wiyanna Mathofani; Aryanti, Dina; Manalu, Tahan Adrianus (Universitas Prima Indonesia, 2026)
This study was conducted solely on nurses, and to achieve optimal results, all PPA should have been involved. The bedside handover method is a standard nursing care handover system in hospitals designed to foster quality interaction and communication between patients and nurses, resulting in effective and efficient nursing care. This study examined the effectiveness of bedside handovers in enhancing nurse communication using a nonequivalent control group pretest–posttest design. A total of 64 nurses were included through total population sampling. The intervention group implemented bedside handovers, whereas the control group conducted handovers at the nurse station. Nurse communication levels were assessed using a questionnaire administered before and after the intervention. Changes in communication levels within each group were analyzed using the Wilcoxon test. The findings revealed a significant improvement in nurse communication in the intervention group (p = 0.000), while no significant change was observed in the control group (p = 0.082). Conclusion: Bedside handovers are effective in improving nurse communication in providing nursing care. This research has an impact on patient satisfaction, nurses and reduces the number of adverse events.